PENGUNGKAPAN DIRI DI MEDIA SOSIAL DITINJAU DARI KECEMASAN SOSIAL PADA REMAJA - Akbar, Zarina; Faryansyah, Robby (IKRAITH-HUMANIORA, 2018)
The study aims to determine the effect of social anxiety towards self disclosure in social media onadolescents. The study with the total of 201 respondents using expost facto quantitative research method withpurposive sampling. The data collection technique using Jourard Self Disclosure (JSDQ) and Social AnxietyScale for Adolescents (SAS-A) as the questionnaire. Statistical analysis for testing the hypothesis is one predictorregression. The result showed that there is no effect of social anxiety towards self disclosure in social media onadolescents which has been proved by F = 0,504 ; p = 0,478 > 0,05.